POTENSI EKSTRAK BUNGA KAMBOJA (PLUMERIA SP.) DAN BUNGA KLUWIH (ARTOCARPUS CAMANSI) SEBAGAI BIOLARVASIDA NYAMUK ANOPHELES SP. DALAM UPAYA PENCEGAHAN PENYAKIT MALARIA - Luh Gde Sri Adnyani Suari; Abiyyu Didar Haq; Luh Ade Dita Rahayu (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
ABSTRACT Background: Malaria is one of many health problem that attracts attention in a lot of countries, especially Indonesia as a tropical country. To minimalize the spread of malaria, many efforts is done to control Anopheles sp as the vector of malaria. Some of many effort that has been done to control malaria is larvaciding. Conventional insecticide such as malathion, DDT, and pyrethroid that is widely used for vector control is known to cause problem such as pollution, residual effect, and resistance of the mosquitoes. Therefore, it is very much needed to find an alternative of the overuse of insecticide and find a better and safer solution both for us and for the environment . Methods: This literature review used a variety of sources that are being retrieved from online publication portal. Discussion: Extract of Plumeria sp. ‘s flower showed the existance of steroid, alkaloid, flavonoid, glycoside, tannin, and essential oil. Steroid, flavonoid, and alkaloid substance are the substances that is expected to have the larvicidal effect. Steroid is able to restrict insect’s growth in the transition phase from larvae to pupae and vice versa. Flavonoid works as a respiratory toxin. Alkaloid acts as a contact toxic and inhibits the acetylcholinesterase which will cause a bitter taste which then interrupts the mealtime of the larvae. Meanwhile Artocarpus camansi contains a substances such as saponin, flavonoid, and polyphenol whose effect is lowering the appetite, inhibiting the respiratory system, and inhibiting the moulting hormone. Conclusion: The combination of kamboja flower (Plumeria sp.) and kluwih flower (Artocarpus camansi) has a potential to be used as biolarvacide of Anopheles sp. Keywords: Kamboja, Kluwih, Biolarvacide, Malaria